Influence of Phase Structure of TiO2 Nanoparticles on Resistive Switching Devices - Benchapol Tunhoo; Direklit Chantarawong; Thutiyaporn Thiwawong; Korakot Onlaor (Current Applied Science and Technology, 2023)
In this work, the electrical memory properties of a bi-stable device based on the structure of aluminum/poly (9-vinyl carbazole) (PVK): TiO2 NPs/indium-tin-oxide (ITO) were reported. The effects of the modified phase structural of titanium dioxide nanoparticles (TiO2 NPs) on the electrical memory characteristics were determined. The TiO2 NPs were annealed at different annealing temperatures. The physical properties of the annealed TiO2 NPs were characterized by transmission electron microscope and X-ray diffraction, which revealed the composition and structure of the anatase and rutile phases. Current-voltage measurements showed that the bi-stable characteristics were affected by the phase structure of the TiO2 NPs. The ON/OFF current ratio of the fabricated device was noted to be approximately 2.06×105 in the case of TiO2 NPs annealed at 500°C. A theoretical model was used to explain the charge injection mechanisms of the device. Moreover, the temperature dependence and retention-time measurements of the device were demonstrated.
Keywords: Advanced Memory and Neural Computing; Conducting polymers and applications; Transition Metal Oxide Nanomaterials